Management of project and activities in a regional line agency - Balanon, Rowie Red N. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2023)
This mixed methods research specifically sequential explanatory design assessed and analyzed the level of knowledge and extent of implementation in Project Management of the focal persons of Dep Ed-Regional Office I. Specifically, along Project Conception and Initiation, Project Execution, Project Performance and Control, and Project Close. Moreover, it also identified the different factors contributing to the encountered difficulties in Project Management. The respondents were the thirty-nine focal persons of the various projects being implemented in Dep Ed-Regional Office I. The data gathered were treated using weighted mean and ranking. The level of knowledge and extent of implementation in Project Management of local persons is Slightly Knowledgeable and Partially Implemented. Unawareness on the process of procurement, inspection and acceptance, and request of needed supplies and materials, lack of trainings involving the procurement process, unaware on the different guidelines in planning and budgeting, and not well-verse in the forms being used were the most factors contributing to the encountered difficulties in Project Management. A thematic model and a Manual on Procedures and Guidelines (MOPG) was crafted and developed to improve the level of knowledge and extent of implementation in Project Management of focal persons.
References: pages 210-217.
CHED-La Union
Keywords: Management